T2 Effect of incident heart failure on short- and long-term mortality of COPD patients. (12th November 2019) - Axson, EL; Sundaram, V; Bloom, CI; Bottle, A; Cowie, MR; Quint, JK
Abstract : Introduction and objectives: Chronic obstructive pulmonary disease (COPD) patients are at a greater risk of developing heart failure (HF), yet HF diagnosis is delayed in COPD patients due to their shared signs and symptoms. HF patients in the general population have seen improved 1-year and 5-year survival post-HF diagnosis 1 ; however, it is well known that cardiovascular comorbidities are systemically under-treated in the COPD population and that COPD patients are diagnosed with HF later than the general population. 2 It may be that COPD patients with incident HF (COPD-iHF) have not seen similar survival gains as the general population. Methods: COPD-iHF patients were identified from the Clinical Practice Research Datalink (CPRD). Age- and sex-adjusted mortality rate ratios (aMRR) for 1-year, 5-year, and 10-year mortality were calculated for COPD-iHF in 2006, 2011, and 2015 compared temporally and to COPD patients without incident HF (COPD-no HF). Results: We identified 181, 705 COPD patients without HF at the start of follow-up. COPD-iHF experienced three times greater 1-year mortality (2006: aHR 3.31, 95%CI: 2.70, 4.06) and two times greater 5-year (2006: aHR 2.35, 95%CI: 2.08, 2.66) and 10-year mortality (2006: aHR 1.95, 95%CI: 1.75, 2.17) than COPD-no HF patients and this did not change based on year of HF diagnosis. 1-year and 5-year mortality did not improve over time comparing COPD-iHF in 2011 (1-year aHR 0.97, 95%CI: 0.74, 1.27; 5-year aHR 1.07, 95%CI: 0.90, 1.26) and 2015 (1-year aHR 1.11, 95%CI: 0.83, 1.50) to COPD-iHF in 2006 (figure 1). Conclusions: COPD-iHF patients have not seen the same survival gains over the past decade as the general population with incident HF. This may reflect continued under-treatment of cardiovascular conditions and the delayed diagnosis of HF within the COPD population. The absence of or delayed access to survival modifying cardiovascular medications in the COPD population with HF may account for the lack of survival gains in this population. Bespoke guidelines for the diagnosis and management of HF in the COPD population are needed to improve survival of patients. References: Taylor, et al. BMJ 2019;364:1223. Hayhoe, et al. Heart 2019;105 (9):678685.